Approval and disapproval of textbooks in the late Ottoman Empire. Issue 1 (2nd January 2017) - Açıkgöz, Betül
Abstract: During the rapidly changing political atmosphere of the 1910s, the practice of sanctioning scholastic knowledge began to be implemented in the yearly selection of textbooks due to political contingencies. The study shows the procedures of approval and disapproval practised by the Grand Council of Education and the Copyright and Translation Office through archival pursuit in the Ministry of Education. The basis of the research material is constituted by documents of the textbook selection commissions for approval and disapproval practices, and rejection petitions written by textbook authors, as well as the incorporation of supportive primary sources such as records of parliament sessions, and critical books and articles on education from the Second Constitutional Period (1908–1918). Tracing a path through the Ottoman archives, the study pursues the frictions between the authors and the Office in the political ambience of the period and exposes the inefficiency of modern bureaucratic units crippled by favouritism and corruption. Thus, it reveals that the well-organised curricula and guidelines in modern schooling did not always yield uniformity. It contributes to questioning the overemphasised impact of modernisation of education, which is often associated with a smooth progression in the history of education literature.